2013
DOI: 10.2174/156800961131300092
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Prion and Prion-Like Proteins in Cancer Development, Progression and Multi-Drug Resistance

Abstract: Prions are renowned for their role in neurodegenerative diseases in humans and animals. These are manifested as transmissible spongiform encephalopathies (TSEs) that result from the conversion of the normal glycosylphosphatidylinositol (GPI) anchored cellular prion protein (PrP(c)) to a misfolded, aggregated and pathogenic form, prion protein scrapie (PrP(Sc)) via a post-translational process followed by the accumulation of PrP(Sc) within the central nervous system. New research in this area has demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…; Hinton et al . ). PrP is ubiquitously expressed by most, if not all cell types in mammals, and is a prominent protein in the brain (Prusiner ).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…; Hinton et al . ). PrP is ubiquitously expressed by most, if not all cell types in mammals, and is a prominent protein in the brain (Prusiner ).…”
mentioning
confidence: 97%
“…The pathogenic and infectious form of prion protein (PrP), the so-called scrapie form, plays a crucial role in the development of transmissible spongiform encephalopathies, such as Creutzfeldt-Jakob disease, Gerstmann-Str€ aussler-Scheinker syndrome, kuru and familial fatal insomnia, and is also involved in non-transmissible neurological disorders, such as Alzheimer's disease (Collinge 1997;Vana et al 2007). The cellular, non-pathogenic form of PrP has been implicated in protective functions against oxidative stress, hypoxia, ischemia, excitotoxicity, or hypoglycemia, and linked to disorders, such as schizophrenia, bipolar disorder, depression, certain forms of dementia with cerebellar disorder, and cancer (Raeber et al 1997;Walz et al 1999;Vassallo and Herms 2003;McLennan et al 2004;Roucou et al 2004;Weise et al 2004Weise et al , 2006Weise et al , 2008Shyu et al 2005;Spudich et al 2005;Weis et al 2008;Hinton et al 2013).…”
mentioning
confidence: 99%
“…Overexpression of PrP is proposed to be closely associated with poor prognosis of pancreatic and breast cancers, highlighting that PrP may affect the growth and invasiveness of cancers. Study also has demonstrated an important role of overexpression of PrP in the acquisition of multi-drug resistant gastric cancer [8]. However, the profiles of PrP in malignant tumors, such as the patterns in electrophoresis and biochemistry features, are addressed little.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have even proposed that overexpression of PrP is closely associated with the poor prognosis of pancreatic and breast cancers, highlighting that it may affect the growth and invasiveness of cancers (16). PrP expression is also believed to play an important role in the acquisition of multidrug-resistant (MDR) gastric cancer (17). However, the expression of PrP and its role in HNSCCs remain undescribed.…”
Section: Introductionmentioning
confidence: 99%